The Relationship of Knowledge and Attitude Towards Hand Washing Behavior in Baiturrahmah Dental Hospital During the Covid-19 Pandemic - Amirah Dinah; Hanim Khalida Zia; Valendriyani Ningrum (Denta Journal Kedokteran Gigi, 2023)
Bacground: Dental practice is very susceptible to nosocomial infections. One of the infection control prevention efforts that can be done is by washing hands. Hand washing is a process that removes dirt on the hands by using a detergent containing an antiseptic agent and running water. Objective: To determine the relationship between knowledge and attitudes towards hand washing in professional students at Baiturrahmah Dental Hospital during the COVID-19 pandemic. Method: This research was a type of quantitative research using observational analytic method with a cross-sectional design. This research was conducted at Baiturrahmah Dental Hospital which was held in November–December 2021. The sampling technique in this study was consecutive sampling. The number of sampels in this study was 80 sampels. Research through the google form given by researchers to research respondents. Result:This study indicated that most of the respondents have good knowledge of hand washing (91.2%), good hand washing attitudes (99.0%), and good hand washing behavior (100.0%). The correlation analysis test was carried out using the Pearson correlation test for parametric analysis and the Spearman correlation test for non-parametric analysis. There was a significant relationship between knowledge of hand washing behavior (p<0.05) and attitudes towards hand washing behavior (p<0.05). Conclusion: There was a significant relationship between knowledge of handwashing behavior in professional students at Baiturrahmah Dental Hospital and there is a significant relationship between attitudes towards handwashing behavior in professional students at Baiturrahmah Dental Hospital.